Immigrants in America: Vain Invaders or Active Partners the Making of the Promised land - AHOUANGANSI, S . Raoul (My University, 2017)
This article aims at grasping a fuller comprehension of “immigrant” in American history. In an effort at apprehending him/her as a vain invader in the “Promised land” or a gem in the making of the later one, this research study clearly sets out to see at depths, the part he happened to play in such an endeavor. Drawing on from immigration , ethnic group impacts in American life experience to the American cultural character itself , it comes out to the conclusion that: immigrants represent in many respects, the most persistent
Keywords: Immigrant - vain invader -promised land – ethnic group.